Ion currents registration through LCC-channels of the nuclear membrane: a chronobiological aspect - Тарнопольська, О.; Котлярова, А. (Київський національний університет імені Тараса Шевченка, 2020)
For seven years of researching the transport systems of nuclear membranes using the patch-clamp method, we observed a certain pattern: in winter, this method's efficiency significantly decreased. Since different seasons are characterized by different light and temperature indicators, we decided to pay attention to the latter's possible impact on the success of the research. Therefore, the purpose of this work was to test the influence of seasonal factors such as changes in daylight hours, temperature, atmospheric pressure, precipitation, and cloudiness on the quality of patchclamp recordings of ion currents through the LCC channels of the nuclear membrane of cardiomyocytes and cerebellar Purkinje neurons. We assumed that with decreasing daylength and decreasing temperature, the patch-clamp registrations' qualitative and quantitative indicators also decrease. We applied Pearson's correlation analysis with initial data on daylight hours, meteorological conditions, and calculated progress of registrations (%) for a specific day to test this assumption. Based on the results of this analysis, we found out that there is a direct pronounced linear dependence of the quality and number of registrations on the length of daylight hours (r = 0.6) and temperature (r = 0.6), as well as a weak inverse dependence on cloudiness (r = 0.3). Analysis of variance (ANOVA) also confirmed a significantly greater success of registrations performed in the summer compared to the winter of the same year. The obtained results can become the basis for optimizing the research activities of working groups studying intracellular transport systems' functioning by electrophysiological methods, in particular, patch-clamp.

Протягом семи років досліджень транспортних систем ядерних мембран із застосуванням методу patch-clamp спостерігали певну закономірність: узимку ефективність роботи цим методом значно знижувалась. Оскільки різні сезони/пори року характеризуються різними світловими і температурними показниками, то ми вирішили перевірити ймовірний вплив останніх на успішність виконання досліджень. Тому метою цієї роботи було перевірити вплив таких сезонних факторів, як зміна тривалості світлового дня, температура, атмосферний тиск, кількість опадів і хмарність на якість patch-clamp-реєстрацій іонних струмів крізь LCC-канали ядерної мембрани кардіоміоцитів і нейронів Пуркіньє мозочка. Ми припустили, що зі зменшенням тривалості світлового дня і зниженням температури зменшуються якісні та кількісні показники patch-clamp-реєстрацій. Для перевірки цього припущення застосовано кореляційний аналіз Пірсона із вихідними даними про тривалість світлового дня, метеорологічні умови та розрахованою успішністю реєстрацій (%) за конкретний день. На основі результатів такого аналізу встановлено, що існує пряма виражена лінійна залежність якості та кількості реєстрацій від тривалості світлового дня (r = 0,6) і температури (r = 0,6), а також слабка обернена залежність від хмарності (r = 0,3). На основі дисперсійного аналізу (ANOVA) підтверджено достовірно більшу успішність реєстрацій, виконаних у літній період, порівняно із зимовими того самого року. Отримані результати можуть стати основою для оптимізації дослідницької діяльності робочих груп, які вивчають функціонування внутрішньоклітинних транспортувальних систем електрофізіологічними методами, зокрема patch-clamp.
Реєстрація іонних струмів крізь LCC-канали ядерної мембрани: хронобіологічний аспект
Keywords: біоритми; хронобіологія; метеорологічні умови; patch-clamp; ядерна мембрана; іонні канали; LCC-канали; biorhythms; chronobiology; meteorological conditions; nuclear membrane; ion channels; LCC channels